Effect of Gender on Patients with Non-Small-Cell Lung Cancer Treated with Immune Checkpoint Inhibitors: A Real-World Study - Teresa Calleja-Chucla; Patricia Cordeiro González; Alejandro Martínez Pradeda; Sonia Pértega-Díaz; Luis Margusino-Framiñán; Silvia Antolín Novoa (Biomedicines)
Objective: To evaluate the differences in overall survival (OS) and progression-free survival (PFS) between men and women with non-small-cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs) in second-line and later treatments. Methods: A retrospective, single-center observational study was conducted on patients with advanced NSCLC treated with ICIs (nivolumab, pembrolizumab, and atezolizumab) from January 2015 to December 2019 (with follow-up until December 2021). Demographic, clinical, and treatment-related variables were collected. OSand PFSwere analyzed using the Kaplan–Meier method and compared between genders using the log-rank test.A multivariate Cox regression analysis was performed to adjust for confounders. Results: A total of 189 patients were included, and 47 (25%) were women. The most common histology was adenocarcinoma (61%). Women began treatment at a younger age (59.8 vs. 66 years, p < 0.001) and had higher rates of active smoking (46.8% vs. 38%, p = 0.001). The median OS was similar between men (9.5 months, 95% CI: 7.1–11.8) and women (9.2 months, 95% CI: 3.3–15.2; p = 0.382) while PFS was significantly higher in males (3.2 months, 95% CI: 2.5–4.0) than in females (2.1 months; 95% CI = 1.6–2.5) (p = 0.002).Women had higher rates of tumor cachexia (BMI < 20).Worse PFS was observed for women both in the <20 kg/m2 (median PFS: 1.8 vs. 2.7 months, p = 0.016) and 20–24.9 kg/m2 groups (median PFS: 2.2 vs. 3.3 months, p = 0.077), while in patients with a BMI >= 25 kg/m2, median OS was higher in women than in men (14.7 months vs. 10.1 months). Women had also a significantly worse PFS than men among those with a cumulative tobacco consumption of <30 packs-year (median PFS: 2.2 vs. 3.2, p = 0.038. In the multivariate analysis, the male sex was significantly associated with a better PFS(HR = 0.59; p = 0.009), without significant differences between sexes in OS (HR = 0.90; p = 0.618). Among the other variables analyzed, only an ECOG >= 2 was significantly associated with both worse OS (HR = 3.53; 95% CI = 1.93–6.47) and PFS (HR = 2.19; 95% CI = 1.23–3.89). Women who discontinued due to toxicity (n = 7) had a median OS of 41.4 months (95% CI: 14.7–68.1) after discontinuation, whereas men (n = 15) had a median OS of 8.8 months (95% CI: 6.9–10.8), (p = 0.045). Conclusions: Sex-based differences were observed in the ICI outcomes. Women had worse PFS, particularly with lower BMI and lower tobacco exposure, despite similar OS between sexes. Women discontinued ICIs due to toxicity earlier but showed longer OS after discontinuation. Poor ECOG status was linked to worse outcomes across all the patients.